Analysis of Individual Factors on Employees’ Perception towards Safety Culture in the Malaysian Manufacturing Industry - Noor Aina Amirah, Mohd Noor; Wan Abd Aziz, Wan Mohd Amin; Wan Izatul Asma, Wan Talaat; Mohd Shaladdin, Muda (2019)
The manufacturing industry has now become one of the most hazardous industries worldwide. Workplace safety remains a field of interest in the manufacturing industry due to the increasing number of accidents in the workplace. Higher number in workplace accidents in this industry has lead to the question of whether the employers commit enough care to the employees’ safety and health in striving to optimize productivity. The objective of this paper is to measure whether there is a significant difference between individual factors towards manufacturing employees’ view regarding safety culture. The target respondents were employees working in the manufacturing industry in Peninsular Malaysia. The quantitative method was applied in this study. The data collected were analyzed using IBM-SPSS Statistics. This study showed that different individual factors are essential in determining safety culture at the workplace. Everyone should be accountable for the prevention of injury at work or for the care of those affected, directly or indirectly. Occupational safety and health (OSH) requires everyone in the workplace to be involved, including employers, employees, their families and the government, to cooperate as a community with the common interest of better prevention and care.